1998
DOI: 10.1172/jci524
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of endothelins-1 and -3, their receptors, and endothelin converting enzyme-1 in the early human embryo.

Abstract: The targeted gene inactivation of endothelins-1 and -3 (ET-1 and ET-3) and of one of their receptors, ETB, in the mouse causes severe defects in the embryonic development. These defects, cardiovascular and craniofacial malformations for ET-1, and colonic agangliogenesis associated with skin pigmentation anomalies for ET-3 and the ETB receptor, reproduce pathological phenotypes due to natural mutations of the same genes in the mouse and the human. The mutant phenotypes have been causatively linked to deficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 30 publications
4
35
0
1
Order By: Relevance
“…superoxide dismutase (Weksler-Zangen et al 2003)), ET-1 concentrations may be up-regulated under mild hyperglycemia levels, and its production may be impaired or its concentrations depleted under severe hyperglycemia. ET-1 is clearly involved in the development of structures derived from neural crest cells, including branchial arch-derived craniofacial tissues, great vessels and cardiac outflow structures in rodents and humans (Kurihara et al 1994, Brand et al 1998, Treinen et al 1999. Thus, the reduced ET-1 concentrations in embryos from severely diabetic rats are likely to be involved in the induction of malformations in neural crest-derived organs detected in embryos from diabetic rats and also in infants from diabetic mothers (Ferencz et al 1990, Siman et al 2000.…”
Section: Control Diabeticmentioning
confidence: 99%
“…superoxide dismutase (Weksler-Zangen et al 2003)), ET-1 concentrations may be up-regulated under mild hyperglycemia levels, and its production may be impaired or its concentrations depleted under severe hyperglycemia. ET-1 is clearly involved in the development of structures derived from neural crest cells, including branchial arch-derived craniofacial tissues, great vessels and cardiac outflow structures in rodents and humans (Kurihara et al 1994, Brand et al 1998, Treinen et al 1999. Thus, the reduced ET-1 concentrations in embryos from severely diabetic rats are likely to be involved in the induction of malformations in neural crest-derived organs detected in embryos from diabetic rats and also in infants from diabetic mothers (Ferencz et al 1990, Siman et al 2000.…”
Section: Control Diabeticmentioning
confidence: 99%
“…Evidence from EDN1 genetic mutants shows that ET and its converting enzyme are necessary for correct vascular development in the embryo. [68][69][70] Huang et al 71 reported that the EDN1 gene was directly involved in hypertension, and polymorphisms in the gene encoding ET receptor-A have been shown to be associated with essential hypertension testifying to the necessity of balance within the system for normal functioning in vascular tissues. 72 While we have reported on the importance of ET-1 expression in retinal microvasculature in high glucose, 73 there appears to be a lack of association between a polymorphism in the EDN1 gene and diabetic retinopathy after correction.…”
Section: Mhc and Immunity Markersmentioning
confidence: 99%
“…Probes for human ECE-1 5 were prepared as described in Korth et al 21 Briefly, the ECE-1 partial cDNA corresponding to the nucleotides 304 to 1666 was linearized by digestion with HindIII to obtain the antisense or with XbaI to obtain the sense RNA. Probes for human ETA 3 and ETB 4 receptors, subcloned into pcDNA3, were prepared as described by Brand et al 26 ETA and ETB cDNA were linearized by digestion with XhoI and KpnI, respectively, to obtain the antisense probes. ETA and ETB cDNA were linearized by digestion with XbaI to obtain the sense probe.…”
Section: Preparation Of Radiolabeled Riboprobesmentioning
confidence: 99%